One of the active ingredients in Paeoniae Radix Alba functions as JAK1 inhibitor in rheumatoid arthritis - Xiao, Lu; Lin, Shudian; Zhan, Feng (Frontiers in Pharmacology, 2022)
Objective. We aimed to explore and verify the mechanism underlying the action of the active ingredients of Paeoniae Radix Alba (PRA) in the treatment of rheumatoid arthritis (RA). Methods. The protein targets of PRA’s six active ingredients and RA were identified. Then, the intersection of the two groups was studied. The drug–target network was constructed, visualized, and analyzed by Cytoscape software. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment were performed to analyze these genes. Furthermore, we validated our predictions of the potential targets through a docking study. Finally, the anti-inflammatory effect of Palbinone (PB), one of the active ingredients of PRA, was tested by conducting in vitro and in vivo studies. Results. Six active ingredients of PRA were identified, and 103 overlapping genes were discovered. Functional enrichment analysis indicated that the genes are mostly enriched in IL-17 signaling pathway, Th17 cell differentiation, and the FoxO, ErbB, and TNF signaling pathways. 10 hub genes and two gene cluster modules were identified by Cytoscape. Molecular docking analysis proved that PB was able to bind to the ATP binding site of Janus kinase (JAK)1, thereby acting as a potential inhibitor of JAK1. In vitro and in vivo studies demonstrated that PB exerts its anti-inflammatory role via the inhibition of JAK1. Conclusions. We constructed a multitarget pharmacological network of PRA in RA treatment. PB, one of the active compounds of PRA, was demonstrated to be a promising inhibitor of JAK1.